Long term follow up of rotator cuff Magnetic resonance imaging changes in patients who underwent acromioplasty without repair of full thickness supraspinatus tendon tears - Chivers, David Andrew (Department of Health and Rehabilitation Sciences, 2016)
Includes bibliographical references